2016
DOI: 10.1097/pgp.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Microcystic Stromal Tumor: A Rare Clinical Manifestation of Familial Adenomatous Polyposis

Abstract: Microcystic stromal tumor (MST) is a rare tumor of presumed sex-cord stromal differentiation. We present a case of MST arising within a patient with constitutional 5q deletion syndrome, whose deletion encompassed the APC gene. Genomic analysis of the MST revealed a point mutation in the remaining APC allele, predicted to result in abnormal splicing of Exon 7. Subsequent clinical investigation revealed multiple gastrointestinal polyps qualifying for a diagnosis of familial adenomatous polyposis. This case empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…In addition to endometrioid ovarian carcinomas, mutations in CTNNB1 are also found in rare cases of mucinous ovarian cancer [38]. Moreover, both CTNNB1 and APC mutations have also been detected in non-epithelial microcystic stromal tumors (MSTs) of the ovary [39,40,41]. Accordingly, an increased incidence of MSTs has also been reported among patients affected by familial adenomatous polyposis (FAP) due to germline mutations in APC [40,41]…”
Section: Wnt Signaling In Ovarian Cancermentioning
confidence: 99%
“…In addition to endometrioid ovarian carcinomas, mutations in CTNNB1 are also found in rare cases of mucinous ovarian cancer [38]. Moreover, both CTNNB1 and APC mutations have also been detected in non-epithelial microcystic stromal tumors (MSTs) of the ovary [39,40,41]. Accordingly, an increased incidence of MSTs has also been reported among patients affected by familial adenomatous polyposis (FAP) due to germline mutations in APC [40,41]…”
Section: Wnt Signaling In Ovarian Cancermentioning
confidence: 99%
“…Additional studies have been published since then, and demonstrated the unique histologic and immunohistochemical features of MCST, including the involvement of the Wnt/β-catenin pathway in the pathogenesis. Nevertheless, to date, less than 40 cases of MCST have been reported worldwide, all of which are described as having benign biological behavior, but one patient experienced recurrence [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…According to our retrospective study, in 26 of 38 cases in which CTNNB1 mutations were detected in the original study and all cases but one exhibited nuclear and cytoplasmic βcatenin immunoreactivity [1][2][3][4][5][6][7][8][9][10][11][12][13][14],which indicates the important role of Wnt/β-catenin in the MCST. In addition, APC mutations were identified in 5 women with MCST, 4 of whom showed clinical features of FAP [2,4,13,14], which explained the strong nuclear immunostaining for β-catenin, although in the absence of β-catenin mutations, further indicating that the Wnt/β-catenin/APC pathway mediated the occurrence and development of MCST. In the present study, however, an oncogenic missense mutation (c.98C > G) in CTNNB1 was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a small number of cases of ovarian MCST had been reported in patients with familial adenomatous polyposis (FAP), an autosomal-dominant cancer predisposition syndrome caused by a germline mutation in the adenomatous polyposis coli (APC) gene on chromosome 5q21, illustrating that MCST might be an extracolonic manifestation of FAP. [ 5 , 14 , 15 ] McCluggage et al [ 13 ] found APC mutations occurred in a minority of MCST and were mutually exclusive with CTNNB1 mutation. Such results explained the nuclear staining with β-catenin in their all cases including those without CTNNB1 mutation, because either CTNNB1 or APC mutation could result in aberrant nuclear and cytoplasmic accumulation of β-catenin.…”
Section: Discussionmentioning
confidence: 99%